Advances in halide ion-mediated advanced oxidation processes for high-salinity wastewater treatment: Mechanisms of reactive oxidative species transformation and halogenated by-product formation - Yu Wang; Bing Yang; Yumin Zhang; Lingli Li; Chao Zhu; Yurui Li; Shaoqing Chen; Lili Ma; Mingyan Chen; Yucheng Liu (Chemical Engineering Journal, 2026)

Comparative genomics of parasitic and symbiotic microeukaryotes: Phylogenomic insights into lifestyle transitions and co-evolutionary dynamics - Yuexin Wang; Yihan Liu; Xiang Wang; Yurui Wang; Tengteng Zhang; Chen Shao (Molecular Phylogenetics and Evolution, 2026)

A novel L-β-Galactoglucan alleviates physical fatigue by modulating load-specific metabolic pathways via the gut–muscle Axis - Jun He; Lingling Du; Meng Wang; Yurui Gou; Ziqi Xu; Shubin Yan; Yimiao Feng; Xiaohua Lyu; Jinyao Chen; Lishi Zhang; Xiaomeng Li (Food Research International, 2026)

Research progress on the extraction, purification, biological activity, and applications of polygonatum polysaccharides - Yan Chen; Fengyi Wei; Yurui Chen; Yinping Li; Zhen Tan; Shajie Luo; Cheng Peng (Food Bioscience, 2026)

Integrating aquatic crops into rotation systems enhances soil health and suppresses potential fungal pathogens in greenhouse cucumber production - Jun Xu; Zhuoya Zhao; Liu Pan; Yuan Yao; Zhi Li; Yurui Wang; Yanfeng Li; Xuehao Chen (Applied Soil Ecology, 2026)

Changing characteristics of maize drought in different climate zones of China based on the continuous days without available precipitation - Yue Qi; Heling Wang; Yurui Tang; Yang Yang; Hong Zhao; Funian Zhao; Kai Zhang; Fei Chen; Xingxing Wei; Xiaofeng Yang (Theoretical and Applied Climatology, 2026)

Comprehensive phylogenomic analyses of ciliated protists with a revised classification of the phylum Ciliophora (Eukaryota, Alveolata) - Yurui Wang; Ying Yan; Zhenzhen Yi; Yan Zhao; Qianqian Zhang; Yong Chi; Tengyue Zhang; Weiwei Liu; Mingjian Liu; Borong Lu; Mingzhen Ma; Wenbao Zhuang; et al. (Science China Life Sciences, 2026)

VVFGO: a robust IMU/AHRS/USBL integrated navigation framework with adaptive virtual velocity factor correction for deep-sea docking - Ruiheng Liu; Xinyu Fei; Suohang Zhang; Yurui Zhang; Shipang Qian; Lu Wang; Yanhu Chen; Canjun Yang (Ocean Engineering, 2026)

Revealing the lifecycle evolution of hail-producing deep convective clouds by synergy of multi-source data - Qiang Li; Hongrong Shi; Yurui Xie; Rubin Jiang; Chaoying Wang; Yupeng Teng; Shuo Jia; Jianwei Wen; Disong Fu; Jiefan Yang; Xuehua Fan; Jinqiang Zhang; et al. (Atmospheric Research, 2026)

Isolation of reassortant H5N1 and H5N8 avian influenza viruses from co-infections and their host-dependent replication dynamics - Yuwei Wu; Nuo Xu; Zhifan Li; Zijun Lu; Yurui Dong; Yijie Guo; Ying Bian; Kunlin Li; Chenzhi Huo; Tao Qin; Sujuan Chen; Hui Yang; et al. (Veterinary Microbiology, 2026)

The global APSES transcription factor PeStuA modulates growth, development, stress response, hydrophobicity, patulin biosynthesis and pathogenicity in Penicillium expansum - Yanling Wang; Yurui Wu; Qianrun Liang; Xin Chen; Jinfen Zhu; Wei Li (International Journal of Food Microbiology, 2026)

Mechanistic insight into impacts of Cl− and Br− at high contents on phenol degradation and halogenated by-product formation in O3/H2O2 process - Bing Yang; Shijie Zhou; Xiangfu Huang; Qiang Zhou; Qinchuan Xu; Ying Qiu; Yurui Li; Mengnuo Wang; Yu Wang; Yuming Zhang; Mingyan Chen; Lili Ma; et al. (Process Safety and Environmental Protection, 2026)

A Patient-Specific Computational Model for Neonates and Infants with Borderline Left Ventricles - Yurui Chen; Isao A. Anzai; David M. Kalfa; Vijay Vedula (Annals of Biomedical Engineering, 2026)

A vertical docking system based on the autonomous underwater shuttle for seafloor communication relay - Xiaoyan Zhao; Xinyu Fei; Suohang Zhang; Ning Tan; Zhangpeng Tu; Anzhe Yi; Yurui Zhang; Canjun Yang; Yanhu Chen (Ocean Engineering, 2025)

Bottom-up hierarchical detection of territorial spatial pattern based on multi-source heterogeneous data - Fangxin Chen; Yurui Li; Yansui Liu (Land Use Policy, 2025)

Impact assessment and driving mechanisms of grading and weight distribution methods on spatial zoning - Fangxin Chen; Yurui Li; Yansui Liu (Applied Geography, 2025)

Genotoxicity mode of action exploration of polyethylene glycol terephthalate (PET) acetic acid migration solution under repeated-dose exposure in rats - Liang Wang; Li Cao; Xiaoya Wang; Yufei Liu; Weiwei Zhang; Yurui Gou; Jun He; Jiao Huo; Xiaomeng Li; Jinyao Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Oxidizing agents alter surface reaction pathways in heterogeneous Fenton reactions: Surface electron transfer interactions and altered bond breaking processes in contaminants - Yurui Li; Haoran Wu; Bing Yang; Chao Zhu; Shijie Zhou; Lili Ma; Lingli Li; Mingyan Chen; Heng Guo; Yucheng Liu (Journal of Environmental Chemical Engineering, 2025)

Government subsidy strategies for new energy vehicle charging infrastructure considering consumers’ low-carbon preference: A tripartite evolutionary game model - Songsong Liu; Tingting Li; Yurui Chen; Chang Lyu; Fengyong Zhai (Energy Policy, 2025)

Technoeconomic and life-cycle assessment of biomass-to-hydrogen conversion via a compact fluidized bed calcium looping gasifier - Qiwei Luo; Jixin Li; Yurui Wang; Rongjie Chen; Shiyi Chen; Wenguo Xiang (Bioresource Technology, 2025)

Spatial-temporal evolution and coupling coordination of land use functions across China by fusing multiple-source heterogeneous data - Fangxin Chen; Yurui Li; Yansui Liu (Land Use Policy, 2025)

Succulent and no-succulent plants in desert grassland ecosystems differ in their leaf traits - Yurui Zhang; Lijuan Chen; Feifei Dong; Ziyue Li; Zhi Zheng (Plant and Soil, 2025)

Effect of CFEM proteins on pathogenicity, patulin accumulation and host immunity of postharvest apple pathogens Penicillium expansum - Yanling Wang; Jie Gao; Xin Chen; Yanqi Huang; Yurui Wu; Jinfen Zhu; Wei Li (International Journal of Food Microbiology, 2025)

Linkage between leaf anatomical structure and key leaf economic traits across co-existing species in temperate forests - Zhi Zheng; Yurui Zhang; Feifei Dong; Lijuan Chen; Ziyue Li (Plant and Soil, 2025)

The clinical characteristics of Streptococcus equi ssp. zooepidemicus causing acute death in pigs and its prevention with chimeric monoclonal antibodies - Chen Yuan; Yuchang Wang; Xiaowen Zhang; Xingyu Tian; Ying Liang; Fei Pan; Haoshuai Song; Linya Xia; Zhihui Wu; Wenqing Wang; Xiaowen Zhang; Yurui Xie; et al. (Veterinary Microbiology, 2025)

Unveiling the neglected impacts of halide ions on phenol removal in UV/H2O2 system: Light shielding and oxidant utilization efficiency - Bing Yang; Ying Qiu; Qiuping Luo; Xiangfu Huang; Yurui Li; Shijie Zhou; Mengnuo Wang; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu (Journal of Water Process Engineering, 2025)

Design of Ni-based heterostructured catalyst with Ni3+ for enhanced bidirectional sulfur conversion - Yurui Wu; Wei Li; Hengzhi Liu; Yufang Chen; Manfang Chen; Xingqiao Wu; Yunfeng Peng; Wenlong Xia; Yuchao Du; Keyang Fu; Xiukang Yang; Xianyou Wang; et al. (Chemical Engineering Journal, 2025)

Extraction optimisation and compositional characterisation of total flavonoids from the Chinese herb tulip: a natural source of antioxidants and anti-inflammatory agents - Jiafeng Ye; Jiamin Cao; Xian Chen; Jingjing Ma; Yangchen Li; Xia Gao; Yurui Zhang; Chunli Wang (Natural Product Research, 2024)

Cumulative effects of cyclic train loading on strains in reinforced soils around tunnels - Jiaofeng Li; Yang Cao; Fasheng Chen; Yurui Lin (Soil Dynamics and Earthquake Engineering, 2024)

Investigation on the rotary atomization evaporation of high-salinity desulfurization wastewater: Performance and products insights - Yurui Wang; Lingxiao Zhan; Qiwei Luo; Heng Chen; Juecen Mao; Jun Wan; Chaozhen Liu; Haijie Chen; Suoqi Zheng; Zhanxing Chen; Zhihao Li; Linjun Yang (Journal of Environmental Management, 2024)

Characterizing energy-related occupant behavior towards urban residential buildings in China with statistical database establishment - Shuqin Chen; Yurui Huang; Jiamin Hu; Shichao Yang; Changqing Lin; Kai Mao; Yue Chen (Energy and Buildings, 2024)

Advances in modified zero-valent iron materials: Synthesis methods, field studies, practical applications and challenges - Yurui Li; Shijie Zhou; Yuan Meng; Ying Qiu; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu; Bing Yang (Chemical Engineering Journal, 2024)

Unveiling the kinetics and mechanism of sulfide-modified zero-valent iron activated hydrogen peroxide for phenol degradation - Bing Yang; Yurui Li; Yuan Meng; Ying Qiu; Mi Zhou; Shijie Zhou; Mengnuo Wang; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu (Journal of Environmental Chemical Engineering, 2024)

Thermal properties and grey correlation degree analysis of tar-rich coal under cryogenic and pyrolysis condition - Tao Xu; Yurui Lei; Lingyun Chen; Yongping Wu (Fuel, 2024)

Effects of Environmental Enrichment on the Growth, Gonadal Development, and Welfare of the Chinese Hooksnout Carp (Opsariichthys bidens) - Yurui Lin; Qianhui Li; Zhuo Cai; Jiazheng Ye; Wanqing Tong; Siqi Ren; Xinrui Wu; Huixian Chen; Meidi Lü; Shanjian Zheng (Fishes, 2024)
To investigate the effects of environmental enrichment on the growth and welfare level of the Chinese hooksnout carp (Opsariichthys bidens), an experiment was carried out for 56 d with four types of enrichment environments: low-density physical enrichment, high-density physical enrichment, low-density social enrichment, and high-density social enrichment. The experimental results revealed that both physical and social enrichment treatments positively affected the growth and gonadal development of O. bidens. The physical enrichment treatment was found to increase the antioxidants’ content, such as CAT, SOD, and GSH, in the liver of O. bidens. Moreover, this treatment was able to lead to a reduction in MDA content and enhancement of the fish’s antioxidant capabilities. Behavioral observations, cortisol level analysis, and pcna gene expression analysis indicated that the physical enrichment treatment redused the clustering, aggression, and stress behaviors of O. bidens, maintaining them in a low-stress state. In most respects, the high-density physical enrichment has more positive effects than the low-density one. In contrast, the social enrichment treatments resulted in higher stress levels for O. bidens.

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Morphology, morphogenesis and molecular phylogeny of a new soil ciliate, Lamtostyla paravitiphila nov. spec. (Ciliophora, Hypotrichia) - Tengteng Zhang; Furui Lu; Xiaoqing Yang; Yurui Wang; Chen Shao (European Journal of Protistology, 2024)

Occurrence states and migration of water during the evaporation of desulfurization wastewater - Lingxiao Zhan; Dawei Hou; Heng Chen; Yurui Wang; Suoqi Zheng; Zhihao Li; Hao Wu; Haijie Chen; Xiaoyue Ma; Linjun Yang (Desalination, 2024)

Freezing pre-treatment improves radio frequency explosion puffing (RFEP) quality by altering the cellular structure of purple sweet potato [Ipomoea batatas (L) Lam.] - Chao Mao; Yurui Chen; Tong Liu; Pengfei Ye; Yequn Wang; Xiangwei Chen; Hongfei Fu; Yunyang Wang; Ke Wang (Food Research International, 2024)

A comparative study of accuracy in major adaptive filters for motion artifact removal in sleep apnea tests - Yongrui Chen; Yurui Zheng; Sam Johnson; Richard Wiffen; Bin Yang (Medical & Biological Engineering & Computing, 2024)
Sleep apnea is probably the most common respiratory disorder; respiration and blood oxygen saturation (SpO 2 ) are major concerns in sleep apnea and are also the two main parameters checked by polysomnography (PSG, the gold standard for diagnosing sleep apnea). In this study, we used a simple, non-invasive monitoring system based on photoplethysmography (PPG) to continuously monitor SpO 2 and heart rate (HR) for individuals at home. Various breathing experiments were conducted to investigate the relationship between SpO 2 , HR, and apnea under different conditions, where two techniques (empirical formula and customized formula) for calculating SpO 2 and two methods (resting HR and instantaneous HR) for assessing HR were compared. Various adaptive filters were implemented to compare the effectiveness in removing motion artifacts (MAs) during the tests. This study fills the gap in the literature by comparing the performance of different adaptive filters on estimating SpO 2 and HR during apnea. The results showed that up-down finger motion introduced more MA than left-right motion, and the errors in SpO 2 estimation were increased as the frequency of movement was increased; due to the low sampling frequency features of these tests, the insertion of adaptive filter increased the noise in the data instead of eliminating the MA for SpO 2 estimation; the normal least mean squares (NLMS) filter is more effective in removing MA in HR estimation than other filters. Graphical abstract

Molecular oxygen activation: Innovative techniques for environmental remediation - Lili Zhou; Yuting Liu; Hao Shi; Yurui Qing; Cheng Chen; Liguo Shen; Mingzhu Zhou; Bisheng Li; Hongjun Lin (Water Research, 2024)

Study on the evaporation performance of concentrated desulfurization wastewater and its products analysis - Yurui Wang; Lingxiao Zhan; Heng Chen; Juecen Mao; Haijie Chen; Xiaoyue Ma; Linjun Yang (Journal of Water Process Engineering, 2024)

Ammonia release characteristics during desulfurization wastewater evaporation: Mechanisms and implications - Heng Chen; Dawei Hou; Zhihao Li; Lingxiao Zhan; Lijian Jin; Suoqi Zheng; Yurui Wang; Hao Wu; Ning Zhao; Liliang Lin; Linjun Yang (Journal of Water Process Engineering, 2024)

Assessing sustainable transformation and development strategies for gully agricultural production: A case study in the Loess Plateau of China - Lulu Qu; Yurui Li; Feng Yang; Li Ma; Zongfeng Chen (Environmental Impact Assessment Review, 2024)

Prediction of urban residential energy consumption intensity in China toward 2060 under regional development scenarios - Shuqin Chen; Yurui Huang; Jiamin Hu; Shichao Yang; Changqing Lin; Kai Mao; Zhiqin Rao; Yue Chen (Sustainable Cities and Society, 2023)

Three closely-related subclasses Phacodiniidia Small & Lynn, 1985, Protohypotrichia Shi et al., 1999, and Euplotia Jankowski, 1979 (Protista, Ciliophora): A new contribution to their phylogeny with reconsiderations on the evolutionary hypotheses - Chunyu Lian; Yan Zhao; Ping Li; Tengteng Zhang; Khaled A.S. Al-Rasheid; Naomi A. Stover; Yurui Wang; Chen Shao (Molecular Phylogenetics and Evolution, 2023)

Rutin hydrate relieves neuroinflammation in zebrafish models: Involvement of NF-κB pathway as a central network - Ying Hu; Kun Jia; Yatong Zhou; Lixin Chen; Fei Wang; Xiaokun Yi; Yong Huang; Yurui Ge; Xiaomei Chen; Dalong Liao; Yuyang Peng; Yunlong Meng; et al. (Fish & Shellfish Immunology, 2023)

Morphological, ontogenetic, and phylogenetic research of a poorly known non-dorsomarginalian ciliate: Erniella filiformis Foissner, 1987 (Protista, Ciliophora, Hypotrichia) - Yurui Wang; Jingyi Wang; Banghe Wang; Kunwu Wang; Chen Shao (European Journal of Protistology, 2023)

Copolymer-grafted cellulose nanocrystal induced nanocomposite hydrogels with enhanced strength, high elasticity and adhesiveness for flexible strain and pressure sensors - Bengang Li; Yurui Chen; Wei Wu; Xuzhi Cao; Zhenyang Luo (Carbohydrate Polymers, 2023)

Belowground facilitation of plant mixtures on rhizosphere soil of Commelina communis grown on extremely Cu- and Cd-contaminated mine: From soil quality to bacterial community - Tan Ke; Huan Wang; Shaofeng Li; Yurui Zhang; Panpan Wang; Chaoqi Chen; Lu Lu; Lanzhou Chen (Applied Soil Ecology, 2023)

Distinguishing anaerobic digestion from electrochemical anaerobic digestion: Metabolic pathways and the role of the microbial community - Nan Wang; Yutong Yang; Kunde Xu; Xiangang Long; Yurui Zhang; Hongzhou Liu; Tiezhu Chen; Jianchang Li (Chemosphere, 2023)

Feasibility analysis of a double-cropping system for the efficient use of farmland on China’s Loess Plateau - Weilun Feng; Yansui Liu; Yurui Li; Zongfeng Chen (Journal of Geographical Sciences, 2023)

Comparative genome analysis of three euplotid protists provides insights into the evolution of nanochromosomes in unicellular eukaryotic organisms - Didi Jin; Chao Li; Xiao Chen; Adam Byerly; Naomi A. Stover; Tengteng Zhang; Chen Shao; Yurui Wang (Marine Life Science & Technology, 2023)
One of the most diverse clades of ciliated protozoa, the class Spirotrichea, displays a series of unique characters in terms of eukaryotic macronuclear (MAC) genome, including high fragmentation that produces nanochromosomes. However, the genomic diversity and evolution of nanochromosomes and gene families for spirotrich MAC genomes are poorly understood. In this study, we assemble the MAC genome of a representative euplotid (a new model organism in Spirotrichea) species, Euplotes aediculatus . Our results indicate that: (a) the MAC genome includes 35,465 contigs with a total length of 97.3 Mb and a contig N50 of 3.4 kb, and contains 13,145 complete nanochromosomes and 43,194 predicted genes, with the majority of these nanochromosomes containing tiny introns and harboring only one gene; (b) genomic comparisons between E. aediculatus and other reported spirotrichs indicate that average GC content and genome fragmentation levels exhibit interspecific variation, and chromosome breaking sites (CBSs) might be lost during evolution, resulting in the increase of multi-gene nanochromosome; (c) gene families associated with chitin metabolism and FoxO signaling pathway are expanded in E. aediculatus , suggesting their potential roles in environment adaptation and survival strategies of E. aediculatus ; and (d) a programmed ribosomal frameshift (PRF) with a conservative motif 5′-AAATAR-3′ tends to occur in longer genes with more exons, and PRF genes play an important role in many cellular regulation processes.

Occupant-centric dynamic heating and cooling loads simplified prediction model for urban community at energy planning stage - Shuqin Chen; Yurui Huang; Xiyong Zhang; Frédéric Kuznik; Xi He; Yuhang Ma; Yuxuan Cai (Sustainable Cities and Society, 2023)

Investigating multi-way impacts of transportation on human footprint: Evidence from China - Shuting Chen; Yurui Li; Zhi Lu; Rui Li; Genying Chang (Environmental Impact Assessment Review, 2023)

Research on COD Soft Measurement Technology Based on Multi-Parameter Coupling Analysis Method - Yurui Zhang; Zhiyong Duan; Anzhe Yi; Jiaqi Hu; Yanhu Chen (Journal of Marine Science and Engineering, 2022)
This paper presents a soft measurement technique for COD (Chemical Oxygen Demand) based on the multiparameter coupling analysis method. First, through mechanism analysis and correlation analysis of historical data during the measurement process, water quality parameters, such as hydrogen potential (PH), dissolved oxygen (DO), turbidity (TU), and electrical conductivity (EC), can be used to estimate COD values. To further improve the estimation accuracy of the water quality parameter model, we adopted a modeling method combining a BP neural network and support vector machine, which showed an average relative error of 6.13% and an absolute coefficient of up to 0.9605. Finally, experiments in a lake environment demonstrate that this method shows excellent performance, with highly reliable and accurate prediction results.

Whole Genomic DNA Methylation Profiling of CpG Sites in Promoter Regions of Dorsal Root Ganglion in Diabetic Neuropathic Pain Mice - Wen Chen; Ting Lan; Qingyu Sun; Yurui Zhang; Danmin Shen; Tingting Hu; Jing Liu; Yingzi Chong; Peipei Wang; Qian Li; Weihua Cui; Fei Yang (Journal of Molecular Neuroscience, 2021)

Systematic positions and taxonomy of two new ciliates found in China: Euplotes tuffraui sp. nov. and E. shii sp. nov. (Alveolata, Ciliophora, Euplotida) - Chunyu Lian; Yurui Wang; Jiamei Jiang; Qingxiang Yuan; Saleh A. Al-Farraj; Hamed A. El-Serehy; Weibo Song; Thorsten Stoeck; Chen Shao (Systematics and Biodiversity, 2021)

Systematics and Multi-Gene Phylogeny of the Subfamily Nothoholostichinae (Ciliophora, Hypotrichia), With Integrative Description of a New Marine Species Nothoholosticha luporinii n. sp. - Tengyue Zhang; Yurui Wang; Ting Cheng; Jiyang Ma; Peter Vd’ačný; Weibo Song; Chen Shao (Frontiers in Marine Science, 2020)
Morphogenesis of ciliated protists attracts a lot of attention, because their huge morphological diversity is related to formation of ciliary structures during cell division. In the present work, the morphology and morphogenesis as well as the phylogenetic position of a new, marine hypotrich ciliate, Nothoholosticha luporinii n. sp., were investigated. The new species is characterized by having a combination of the following features: a bicorona whose anterior row contains four frontal cirri and posterior row includes only two cirri, a single buccal cirrus, midventral complex composed of about 30 cirral pairs, one pretransverse cirrus, 3–6 transverse cirri, one left and one right marginal cirral row; three bipolar dorsal kineties; contractile vacuole located in about 2/3 of the body length, two types of cortical granules, and many macronuclear nodules scattered throughout the cytoplasm. The morphogenesis of N. luporinii follows the ontogenetic mode of Pseudokeronopsis , a well-known and closely related genus except that the macronucleus fuses into a single mass in the middle fission stage. Phylogenetic analyses based on the rDNA operon classify Nothoholosticha in the family Pseudokeronopsidae and support the distinctness of the new taxon as well as the monophyletic origin of the subfamily Nothoholostichinae.

The VALiDATe29 MRI Based Multi-Channel Atlas of the Squirrel Monkey Brain - Kurt G. Schilling; Yurui Gao; Iwona Stepniewska; Tung-Lin Wu; Feng Wang; Bennett A. Landman; John C. Gore; Li Min Chen; Adam W. Anderson (Neuroinformatics, 2017)

Study on dealkalization and settling performance of red mud - Muxi Luo; Xuejiao Qi; Yurui Zhang; Yufei Ren; Jiacheng Tong; Zining Chen; Yiming Hou; Nuerxiate Yeerkebai; Hongtao Wang; Shijin Feng; Fengting Li (Environmental Science and Pollution Research, 2017)

Enzymatic and chemical mapping of nucleosome distribution in purified micro- and macronuclei of the ciliated model organism, Tetrahymena thermophila - Xiao Chen; Shan Gao; Yifan Liu; Yuanyuan Wang; Yurui Wang; Weibo Song (Science China Life Sciences, 2016)

Progress of research on urban-rural transformation and rural development in China in the past decade and future prospects - Yansui Liu; Hualou Long; Yufu Chen; Jieyong Wang; Yurui Li; Yuheng Li; Yuanyuan Yang; Yang Zhou (Journal of Geographical Sciences, 2016)

Dynamic trends and driving forces of land use intensification of cultivated land in China - Guogang Wang; Yansui Liu; Yurui Li; Yangfen Chen (Journal of Geographical Sciences, 2015)